Effect of stocking density on growth, feed utilization and survival of an endangered Tor khudree fry in floating cages in a tropical reservoir - Subuddhi, U. K.; Das, A. K.; Choudhary, R. K.; Mishal, P.; Biswas, N. (Journal of the Inland Fisheries Society of India, 2021)
An experiment was conducted to evaluate the effects of stocking density on growth, survival rate and feed conversion ratio of fry of Tor khudree, an endangered fish reared at three different densities in the floating cages installed in Kerwa reservoir, Madhya Pradesh, India. The fish fry (36.37mm, 0.71g) were stocked in three different stocking densities (0.07, 0.14 and 0.21 kg m-3 respectively corresponding to treatments T1 (100 nos. m-3), T2 (200 nos. m-3), and T3 (300 nos. m-3). The growth data were collected fortnightly and the experiment was conducted for 120 days. Fish were fed with commercial feed (crude protein 26-35%) thrice a day @8-10% of the body weight. The final weights of the fish reached weight (mean ± S.D.) of 9.3±1.97 g, 9.18±2.43 g and 4.53±1.42 g in T1, T2 and T3 respectively. The feed conversion ratio and mean survival rates were estimated at 1.48, 1.52 and 2.59, and 78.50, 77.99 and 64.11% respectively in T1, T2 and T3. The study showed that the stocking density of 100 and 200 nos./m-3 had similar growth rate, feed conversion and survival rate revealing an ideal stocking density of 200 nos.m-3 for fingerling raising in cages without affecting the growth, feed utilisation and survival. The present study demonstrates optimum rearing density of Tor khudree fry in enclosure system to promote mahseer culture with better growth and production which would help in conservation of this endangered species.Key words Cage aquaculture, Stocking density, Mahaseer, Kerwa reservoir, M.P., India